Psychological interventions for people with psychotic experiences: protocol for a systematic review and meta-analysis - Soneson, E; Russo, D; Knight, C; Lafortune, L; Heslin, M; Stochl, J; Georgiadis, A; Galante, J; Duschinsky, R; Grey, N; Gonzalez-Blanco, L; Couche, J; et al. (BioMed Central, 2019)
BACKGROUND:Many people who have common mental disorders, such as depression and anxiety, also have some psychotic experiences. These experiences are associated with higher clinical complexity, poor treatment response, and negative clinical outcomes. Psychological interventions have the potential to improve outcomes for people with psychotic experiences. The aims of this systematic review are to (1) synthesise the evidence on the effectiveness and cost-effectiveness of psychological interventions to reduce psychotic experiences and their associated distress and (2) identify key components of effective interventions. METHODS:Our search strategy will combine terms for (1) psychological interventions, (2) psychotic experiences, and (3) symptoms associated with psychotic experiences. We will search the following online databases: MEDLINE, Embase, PsycINFO, all Cochrane databases, British Nursing Index (BNI), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Health Management Information Consortium (HMIC), Education Resources Information Center (ERIC), and EconLit. Our primary outcome is the proportion of people who recovered or remitted from psychotic experiences after the intervention. Our secondary outcomes are changes in positive psychotic symptoms, negative psychotic symptoms, depression, anxiety, functioning (including social, occupational, and academic), quality of life, and cost-effectiveness. Two independent reviewers will judge each study against pre-specified inclusion and exclusion criteria and will extract study characteristics, outcome data, and intervention components. Risk of bias and methodological quality will be assessed using the Effective Public Health Practice Project Quality Assessment Tool for Quantitative Studies and the Drummond Checklist. Results will be synthesised using random-effects meta-analysis and narrative synthesis. DISCUSSION:The identification of effective psychological interventions and of specific components associated with intervention effectiveness will augment existing evidence that can inform the development of a new, tailored intervention to improve outcomes related to psychotic symptoms, anxiety and depression, distress, functioning, and quality of life. SYSTEMATIC REVIEW REGISTRATION:PROSPERO CRD42016033869.